1995
DOI: 10.1093/oxfordjournals.humrep.a136243
|View full text |Cite
|
Sign up to set email alerts
|

Andrology: Polycystic ovary syndrome: the spectrum of the disorder in 1741 patients

Abstract: The criteria for the diagnosis of the polycystic ovary syndrome (PCOS) have still not been agreed universally. A population of 1741 women with PCOS were studied, all of whom had polycystic ovaries seen by ultrasound scan. The frequency distributions of the serum concentrations of follicle stimulating hormone (FSH), luteinizing hormone (LH), testosterone and prolactin and the body mass index, ovarian volume, uterine cross-sectional area and endometrial thickness were determined and compared with the symptoms an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
365
5
40

Year Published

1997
1997
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 933 publications
(433 citation statements)
references
References 0 publications
23
365
5
40
Order By: Relevance
“…Only one woman showed all criteria of the polycystic ovary syndrome (PCO-syndrome: hyperandrogenism, polycystic ovaries, abnormal LH-FSHratio b 2.0). 31 Body weight and height were determined in all 58 subjects. WHR was calculated by dividing the waist circumference at the narrowest place above the umbilicus by the hip circumference at the widest place.…”
Section: Subjectsmentioning
confidence: 99%
“…Only one woman showed all criteria of the polycystic ovary syndrome (PCO-syndrome: hyperandrogenism, polycystic ovaries, abnormal LH-FSHratio b 2.0). 31 Body weight and height were determined in all 58 subjects. WHR was calculated by dividing the waist circumference at the narrowest place above the umbilicus by the hip circumference at the widest place.…”
Section: Subjectsmentioning
confidence: 99%
“…Polycystic ovary syndrome (PCOS) is a common female endocrinopathy with a prevalence of between 5% and 7% in premenopausal women, and frequently co-exists with both obesity and type 2 diabetes mellitus [1][2][3]. Substantial evidence implicates obesity as an important factor in the aetiology of PCOS [4][5][6][7], though the mechanistic links between these conditions and how they interact with type 2 diabetes mellitus are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately~ any discussion on PCOS is hampered by the fact that there is no consensus definition of this, albeit frequent, clinical finding. While some leading groups require the presence of hyperandrogenism (clinical or biochemical) and chronic anovulation together with PCO (4), other authorized groups claim that the polycystic appearance of the ovaries can provide a unifying diagnostic criterion, which is certainly lacking (3,5). In addition, it has been shown that the incidence of PCO in normal subjects is as high as 23% (6).…”
Section: Introductionmentioning
confidence: 99%